Colchicine for COVID-19 in adults in the community (PRINCIPLE): a randomised, controlled, adaptive platform trial - PRINCIPLE Trial Collaborative Group; Dorward, J; Yu, L-M; Hayward, G; Saville, B; Gbinigie, O; Van Hecke, O; Ogburn, E; Evans, P; Thomas, NPB; Patel, M; Richards, D; et al. (Cold Spring Harbor Laboratory Press, 2021)
Objectives Colchicine has been proposed as a COVID-19 treatment, but its effect on time to recovery is unknown. We aimed to determine whether colchicine is effective at reducing time to recovery and COVID-19 related hospitalisations/deaths among people in the community.